Community Compliance to The Health Protocol During The Covid-19 Pandemic in The Ciamis Community Health Center - ana samiatul millah (Insights in Public Health Journal, 2021)
Corona virus diseases 2019 currently a problem in all countries in the world. Knowledge about outbreaks and health protocol rules on adapting normal habits in the community is still very lacking. The method in this research is quantitative analytic with cross sectional approach. The sample of this research is people aged 17-60 years in the Work Area of ​​the Ciamis Health Center, Ciamis Regency for the period January-March 2021. 100 people with proportional random sampling technique. The results showed that most of the public's knowledge about the new normal health protocol during the Covid-19 pandemic was still lacking as many as 55 people (55%) most of the respondents did not comply with the new normal health protocol during the Covid-19 pandemic as many as 63 people (63%) ). So there is a significant relationship between knowledge and public compliance with the new normal health protocol during the COVID-19 pandemic in the Ciamis Health Center Work Area in 2021 because the value of chi square (χ2) count > chi square (χ2) table (54.863 > 5.991) and the value of chi square (χ2) > value (0.05 > 0.001). It is hoped that the public will further increase their understanding of the new normal health protocol during the Covid-19 pandemic by participating in various counseling from health workers.